The Direct Organogenesis In Local Clones Of Patchouli Plant( Pogostemon cablin Benth)InVitro - Reni Mayerni (JERAMI : Indonesian Journal of Crop Science, 2020)
Background and Objective: The purpose of this research is to get to be able to identify local patchouli plants that are able to produce the best plantlets in many concentrations of BAP. Materials and Methods: The research conducted in Laboratory of Tissue Culture Faculty of Agriculture, Andalas University from May until November 2019. The research material used in this study was the accession of patchouli plants in West Sumatra, namely: Situak and method of research is completely randomized design.Results: Concentrations of 0.5 ppm kinetin + 0.5 ppm BAP, 0.5 ppm kinetin + 1 ppm BAP and 1 ppm kinetin + 1 ppm BAP can stimulate organogenesis (bud) in vitro